Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian - Kukuh Mulyanto (Anindyaguna Ekonobisnis : Jurnal Ekonomi dan Bisnis STIE Anindyaguna, 2020)
This study aims to examine the factors that influence the Purchase Decision (Case Study of PT. Advan Speaker in the Candi area of ​​Semarang). This data research uses a questionnaire with a sample of 100 respondents in the Semarang area. This sampling technique uses nonprobability sampling, with one of the methods used is purposive sampling. The data obtained were then analyzed with the SPSS program. The results of this study are: (1) Product quality has a positive and significant effect on purchasing decisions with a t value of 2.213 > 1.66088. (2) Promotion has a positive and significant effect on purchasing decisions with a t value of 2.335 > 1.66088. (3) Price perception has a positive and significant effect on purchasing decisions with a t value of 6.773 > 1.66088. (4) simultaneously product quality, promotion, and price perception have a positive and significant effect on purchasing decisions at PT. Advan Speaker in the Semarang Temple area with an R2 value of 0.573 or 57.3% and the most influential variable is the price perception variable which can be seen from the largest t-count value among other variables